On the stability of solutions of stochastic differential inclusions - Kravets, T. N. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We study the stability in probability of a solution of a stochastic differential inclusion in a finite-dimensional space with nonrandom coefficients and a maximally monotone operator in the drift coefficient.